Political Economy and MUI Fatwa No. 83 of 2023: Literature Review - Agung Prayogo; Rakhmat Syawal; Adi Pia; Devrichan Syahputra Zalukhu; Elly Warnisyah Harahap (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This research is a literature review which aims to analyze the relationship between political economy and MUI Fatwa No. 83 of 2023. Through searching for the keywords "political economy" and "fatwa" using Google Scholar, various relevant journal articles and books were collected, mapped and analyzed. The research results show that MUI Fatwa No. 83 of 2023 has significant implications for economic policy in Indonesia, serving as an ethical and moral guide that influences regulations on sharia banking, halal investment, and other economic sectors. This fatwa emphasizes the importance of fair and sustainable economic practices in accordance with Islamic principles. The conclusions of this research confirm the crucial role of fatwas in shaping Indonesia's political-economic landscape and underscore the need for further research to explore their long-term impact.